Pola Persebaran Permukiman Penduduk di Kecamatan Tanah Sepenggal Kabupaten Bungo - Mu’asri, M.; Febriandi, Febriandi (Lembaga Yasin AlSys, 2025)
This study aims to analyze the spatial distribution patterns of settlements and the factors influencing their distribution in Tanah Sepenggal Subdistrict. A descriptive quantitative approach was employed, with the population based on registered household data in the area. A total of 200 household heads were selected as the sample using simple random sampling with the Slovin formula. Secondary data were obtained from relevant institutions and analyzed using the Nearest Neighbor Analysis (NNA) technique by mapping settlement points to identify spatial patterns. The factors analyzed include strategic location, topography, water availability, public facilities, accessibility, land use, and river setback boundaries. The findings indicate that the settlement distribution pattern in Tanah Sepenggal is categorized as clustered, suggesting a concentration of settlements in specific areas. This pattern results from the combined influence of physical and socio-economic factors that lead communities to choose settlement locations with better access to resources and public services. These findings contribute to sustainable spatial planning that aligns with local geographic characteristics.